Wind energy resources assessment of Cuba using the regional climate model PRECIS in high resolution scenarios of climate change RCPs. Issue 5 (October 2022) - Alonso, Yoandy; Bezanilla, Arnoldo; Alpizar, Milena; Martinez, Yosvany
An analysis of the behavior of the wind speed using the regional climate model PRECIS in high resolution scenarios of climate change RCPs is presented. The projections indicate that throughout the century, the speed of the surface wind will continue to increase to a greater or lesser extent (depending on the scenario) in most of the national territory, mainly towards the coast north, as an intensification and westward shift of the anticyclone North Atlantic could occur. The most important thing about this increase is that allows to consolidate the current projection of the Cuban wind program, in which the construction of 13 wind farms is proposed, precisely where the wind potential of Cuba will be increased. Finally this increase is added to the wind speed outputs of the Numerical Wind Atlas of Cuba to estimate the values of wind speed over the future periods.